Haida totem poles in front of houses, Howkan village, Long Island, Alaska, 1906. - Hunt, Mrs. Forrest
Totem poles sit front of houses in a Kaijani village. The Kaijani are a tribe of the Haida Indiancs. Caption on image: Totem poles at Haida Indian village of Howkan, S. E. Alaska, taken 1906 On verso of image: Original photo by Mrs. Forrest Hunt, Ketchikan. Copied by William Hagevig, 1951 In Garfield Volume 1, leaf 20